Analisis Yuridis Pembubaran Perseroan Terbatas (PT) Yang Tidak Beroperasi - Priscila Patricia Yosephin (Magister Kenotariatan, Universitas Jambi, 2021)
Dissolution of a limited liability company consists of some methods pursuant to Article 142 of Law No. 40/2007 On Limited Liability Companies, one of which is by a court ruling. According to explanation of Article 146 of the Law on Limited Liability Companies, dissolution of a limited liability company with an excuse that it no longer operates has to be proved with a letter submitted to tax agency. However, the law does not mention who is authorized to submit the letter to tax agency. This research analyses the position of directors and stockholders in the process of dissolution of a limited liability company that no longer operates, the consideration and ruling handed down by the judge in the Verdict of the Supreme Court Number 1618 K/PDT/2016 and the Verdict of the Constitutional Court No. 63/PUU-XVI/2018 concerning legal certainty of position of director and stockholders related to the process of dissolution of a limited liability company that no longer operates, and the legal protection for stockholders in case the director fail to perform their duties and report to related institutions in the process of dissolution of a limited liability company. This research employs normative juridical method and is juridical analytical. The data are collected through library research conducted by document study. The data analysed qualitatively and the conclusion is drawn deductively. The juridical analysis demonstrate that concerning the dissolution of a limited liability company that no longer operates in the Verdict Number 1618 K/PDT/2016, the Panel of Judges state that the director is rightful to submit a letter related tax agency regarding that the limited liability company no longer operates. In relation with the explanation of article 146 paragraph 1 letter C o the Law on Limited Liability Companies in the Verdict No. 63/PUU-XVI/2018, the Panel of Judges state that the explanation is not unconstitutional an has provuded adequate explanation that although director is not mentioned as the organ of a limited liability company that shall submit the letter to tax agency concerning its non-operating company, it has to be clearly understood that the Law on Limited Liability Companies delegate the responsibility of organization of the company only to the director. With this anlysis, it is suggested that more assertive and clear regulations be made in order to prevent various interpretations patricularly in understanding the explanation of the Law No. 40/2007 on Limited Liability Companies.